Pemberdayaan Ibu PKK melalui Inovasi Produk Yogurt Kacang Hijau untuk Pencegahan Stunting - Sari, Mulia Safrida; Niaci, Sarah; Mastura, Mastura; Amna, Ulil; Fitriani, Fitriani; Wibowo, Sara Gustia; Lestari, Ratna; Sari, Herlina Putri Endah; Faizah, Siti (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
Efforts to prevent stunting at the village level require contextual and innovative strategies, particularly by involving community empowerment in improving children's nutritional quality. This community service program was implemented in Tanjung Seumantoh Village, Karang Baru Subdistrict, Aceh Tamiang Regency, in response to the high percentage of families at risk of stunting (19.96%) and the low consumption of nutritious food caused by limited nutritional knowledge, high milk prices, and cases of lactose intolerance. The main objectives of this program were: (1) to enhance PKK mothers’ knowledge of balanced nutrition and the importance of adequate nutrient intake in preventing stunting, (2) to develop their skills in producing yogurt fortified with mung bean flour as a nutritious food product, and (3) to encourage the utilization of local food sources at the household level to support children's growth and development. The methods included an initial community assessment, nutrition education sessions, yogurt production training, post-activity evaluation through questionnaires, and follow-up mentoring. The results showed a significant increase in knowledge, with 84% of respondents demonstrating improved understanding of the nutritional benefits of mung beans as a fortifying ingredient in milk-based products. Additionally, a portion of respondents showed greater awareness of the relationship between child nutrition and stunting prevention (scale 5; 4.52±0.51), and most participants agreed that they were able to independently follow the steps of milk processing after the training (scale 4; 4.12±0.83). Furthermore, household-level food diversification increased, and 52% of participants were motivated to continue producing fortified yogurt independently. These findings indicate that fortifying UHT milk with mung bean flour through the active involvement of PKK mothers can serve as an effective, sustainable, and community-based strategy for stunting prevention while simultaneously contributing to family economic empowerment.